Co-pyrolysis behaviors of coal and polyethylene by combining in-situ Py-TOF-MS and reactive molecular dynamics. (1st January 2023) - Feng, Wei; Zheng, Mo; Jin, Lijun; Bai, Jin; Kong, Lingxue; Li, Huaizhu; Bai, Zongqing; Li, Wen
Graphical abstract: Highlights: Co-pyrolysis of coal-polyethylene is explored by combining ReaxFF MD and Py-TOF-MS. DTG curves shows that 30% PE addition has the strongest synergistic effect. PE addition alters pyrolyzate contents rather than generates cross-reaction products. ReaxFF MD method reproduces pyrolyzate profiles to complement experimental observations. PE promotes C-C breaking to form more H2 and inhibits C-O breaking to reduce CO2 . Abstract: Co-pyrolysis of waste plastics and low-rank coal is a promising approach to deal with the serious waste crisis and improve the clean utilization of low-rank coal. In this work, the comprehensive co-pyrolysis behaviors of low-rank coal and polyethylene plastics were explored systematically by combining TG experiment, in-situ Py-TOF-MS technique, and ReaxFF MD simulation. The consistent results were obtained among three approaches to demonstrate the positive interaction exists between coal and PE during the co-pyrolysis process, which leads to volatile yield increasing with PE addition. TG experimental results showed that the blending ratio of 7:3 for coal and PE has the strongest synergy during the co-pyrolysis process, while Py-TOF-MS experimental results unraveled that the synergistic effect of coal and PE was determined by changing the content of pyrolysis products rather than by producing cross-reaction products. The PE addition significantly reduced the yield of MAHs and normal alkyl-substituted monophenols and increased the yield of olefins, alkanes, and aromatic derivatives. ReaxFF MD simulation results complement the experimental observation to obtain similar weight loss profiles with TG experiments and consistent identification of major representative tar pyrolyzates with Py-TOF-MS experiments. Particularly, the detailed gas evolving trends and the underlying bond-breaking reactions of CC, CO, and CH bonds were revealed by ReaxFF MD, which indicates PE addition promotes bond breaking of CC and CH to enhance more tar generation. The combination of experiments and ReaxFF MD simulations can capture the comprehension of the co-pyrolysis process between low-rank coal and PE, which can be extended to other co-pyrolysis applications for related solid fuels.